Pyrazole-thermal synthesis: a new approach towards N-rich titanium-oxo clusters with photochromic behaviors. Issue 23 (22nd May 2019) - Fan, Xi; Fu, Hao; Zhang, Lei; Zhang, Jian
Abstract : Pyrazole-thermal synthesis has been developed for preparing N-rich titanium-oxo clusters with diverse photochromic behaviors. Abstract : A novel pyrazole-thermal approach has been successfully developed to synthesize titanium-oxo clusters doped with abundant nitrogen. The coordinated ligands of the obtained clusters have significant effects on their photochromic behaviors.